Fundamental food microbiology - Ray, Bibek (CRC Press, 2003)
"Fundamental food microbiology" includes the latest informartion on microbial stress response, food biopreservatives, recent pathogens of importance (Such as Helicobacter pylori and BSE), and control by novel peocessing technologies.